Financial Development and Sectoral Output: Growth in 19th Century Germany - Frank Westermann; Katharina Diekmann (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2011)
In this paper we re-evaluate the hypothesis that the development of the financial sector was an essential factor behind economic growth in 19th century Germany. We apply a structural VAR framework to a new annual data set from 1870 to 1912 that was initially recorded by Walther Hoffmann (1965). With respect to the literature, the distinguishing characteristic of our analysis is the focus on different sectors in the economy and the interpretation of the findings in the context of a two-sector growth model. We find that all sectors were affected significantly by shocks from the banking system. Interestingly, this link is the strongest in sectors with small, non-tradable goods producing firms, such as services, transportation and agriculture. In this regard, the growth patterns in 19th century Germany are reminiscent to those in today's emerging markets.
Keywords: C22; N13; N23; O11; 330; Economic Growth; Financial Development; Sectoral asymmetries